1989
DOI: 10.1111/j.1365-2125.1989.tb03496.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of cilazapril on indices of autonomic function in normotensives and hypertensives.

Abstract: 1. In two single dose studies, acute blood pressure reduction with cilazapril was not associated with any significant change in supine or erect heart rate in either normotensives or hypertensives. 2. To investigate the lack of reflex cardioacceleration, a series of autonomic function tests was undertaken when there was maximum ACE inhibition, maximum evidence of angiotensin II withdrawal and the lowest blood pressure. 3. There was no evidence that cilazapril had any significant impact on indices of sympathetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1989
1989
1999
1999

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…13 On the other hand, Cilazapril did not alter the heart rate re sponse to All in normal subjects, despite the significant decrease of arterial pressure. In single dose studies, Cila zapril did not modify heart rate, sympathetic nervous activity and baroreflex sensitivity, but enhanced para sympathetic activity, 24 suggesting a withdrawal of the vagolytic actions of AIL Similar findings were reported after administration of other compounds such as Capto pril or enalapril, 14,25 indicating a similar cardiovascular profile for these compounds.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…13 On the other hand, Cilazapril did not alter the heart rate re sponse to All in normal subjects, despite the significant decrease of arterial pressure. In single dose studies, Cila zapril did not modify heart rate, sympathetic nervous activity and baroreflex sensitivity, but enhanced para sympathetic activity, 24 suggesting a withdrawal of the vagolytic actions of AIL Similar findings were reported after administration of other compounds such as Capto pril or enalapril, 14,25 indicating a similar cardiovascular profile for these compounds.…”
Section: Discussionsupporting
confidence: 67%
“…Plasma renin activity, aldosterone, All, and ANP were determined by radioimmunoassay [15][16][17][18] and plasma NE and epinephrine concentrations were ob tained using a radioenzymatic method, 19 as reported elsewhere. 20 Exchangeable sodium was measured by isotope dilution technique using 24 Na. 21 Cardiovascular reactivity was analyzed by calculation of threshold and pressor doses 13,14 and by deriving dose-response curves.…”
Section: Methodsmentioning
confidence: 99%
“…This is considered to be due to attenuation of parasympathomimetic action of A11 by reducing the circulating A11 level; (iii) CEI attenuate the activity of the sympathetic nervous system centrally as well as peripherally (Bravo & Tarazi 1979;Ueno et al 1980;Morioka et al 1983;Polonia et al 1988;Lombardi et al 1989;Fernandez et al 1990;Stead & Bloor 1990). The mechanism of this central action has been shown to be due to reduction in the circulating A11 level and increases in the central prostaglandins and opioids; and (iv) contrary to the notion in (i), some investigators have reported that CEI does not affect baroreceptor function or the autonomic nervous system (Warren et al 1983;Duesing et al 1987;Elliott 1989;Reid & Chou 1990), but rather attenuate the reflex tachycardia due to a reduction of the peripheral effects of A11 (Isaacson & Reid 1990). Whatever, the acute circulatory changes induced by CEI are characterized by the reduction of circulating AII.…”
Section: Introductionmentioning
confidence: 97%
“…Whether administered chronically or acutely, CEI cause less reflex tachycardia than other vasodilating hypotensive agents (Ueno et al 1980). The reasons for this minimal reflex tachycardia have been postulated as follows: (i) CEI stimulate baroreceptor reflexes by reducing the level of circulating angiotensin I1 (AII) because A11 is considered to attenuate baroreflex sensitivity (Mancia et al 1982;Berecek et al 1983;Ebert 1985;Clementi et al 1986;Garner et al 1987;Elliott et al 1989;Lombardi et al 1989;Muratani et al 1990); (ii) CEI stimulate the parasympathetic nervous system (Takeda et al 1987;Crozier et al 1989;Elliott et al 1989;Boni et al 1990). This is considered to be due to attenuation of parasympathomimetic action of A11 by reducing the circulating A11 level; (iii) CEI attenuate the activity of the sympathetic nervous system centrally as well as peripherally (Bravo & Tarazi 1979;Ueno et al 1980;Morioka et al 1983;Polonia et al 1988;Lombardi et al 1989;Fernandez et al 1990;Stead & Bloor 1990).…”
Section: Introductionmentioning
confidence: 99%